PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS MACROMEDIA FLASH UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Nur Asrawati; Mulyati Mulyati (PEDAMATH: Journal on Pedagogical Mathematics, 2018)
This research is a research and development research. The purpose of this study was to develop macromedia flash-based learning media on Space Building material. The process of developing macromedia flash based learning media uses a modified 4-D model from Thiagarajan, which consists of four stages, namely define, design, develop and dessiminate. The desired product in this study is macromedia flash based learning media, learning motivation questionnaire, personality type questionnaire and Mathematics Learning Outcomes Test. The trial was conducted at the Kartika Wirabuana Makassar Vocational School, in class XI students, the results obtained from the trial were macromedia flash based learning media, learning motivation questionnaire, personality type questionnaire and Mathematics Learning Outcomes Test. The results showed that the validity of macromedia flash based mathematics learning media was very valid with a validity value of 0.952 and a reliability coefficient level of 0.976. Validity and learning motivation questionnaire is 1 and reliability coefficient level 1, validity of personality type questionnaire is 1 and reliability coefficient level 1 and learning outcome test is validity is 1 and its reliability level is 1 and macromedia flash based mathematics learning media is very influential on student learning motivation, this is seen from the gain value of 0.39%, and the personality type of students influences student motivation.